Efficacy of Functional Endoscopic Sinus Surgery and Impact of Chronic Lung Disease on its Outcome in Patients of Chronic Rhinosinusitis - Minakshmi Karmakar; V D Prasanna Kumar Vasamsetty; Bonapart Chowdhury (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction